LITERACY CHARACTERISTICS OF CALCULUS AND ITS ROBLEMS IN THE CONTEXT OF COMMUNITY SERVICE - Indeswati Diyatri; Keyona Laila Olivia; Mahela Sefrian Luthfimaidah; Dimas Rudianto Fardha (Universitas Airlangga, 2022)
The prevalence of dental and oral diseases in Indonesia tends to increase. The problem of high rate in dental and oral disease are currently influenced by community behavioural factors. High rate of dental and oral disease was also because of the Indonesian population who realized that they has dental and oral problem is only 23% of population. Community behaviour is closely related to the level of public knowledge about gum health and tartar. Lack of knowledge about gum health and ignorance of the dangers of tartar that caused by dental plaque causing people not to take advantage of dental health services when they have dental plaque and even become inflammation of the gums. That condition, will contribute to poor dental health status of the community. Therefore, this community service is carried out for educate the characteristics of calculus, gum inflammation and the treatment of tartar.